Observation of Same-Sign WW Production from Double Parton Scattering in Proton-Proton Collisions at ?s=13 TeV - Tumasyan, A.; Adam, W.; Andrejkovic, J. W.; Bergauer, T.; Chatterjee, S.; Dragicevic, M.; Del Valle, Escalante (Amer Physical Soc, 2023)
The first observation of the production of (WW +/-)-W-+/- bosons from double parton scattering processes using same-sign electron-muon and dimuon events in proton-proton collisions is reported. The data sample corresponds to an integrated luminosity of 138 fb(-1) recorded at a center-of-mass energy of 13 TeV using the CMS detector at the CERN LHC. Multivariate discriminants are used to distinguish the signal process from the main backgrounds. A binned maximum likelihood fit is performed to extract the signal cross section. The measured cross section for production of same-sign W bosons decaying leptonically is 80.7 +/- 11.2(stat) (+9.5)(-8.6)(syst) +/- 12.1(model) fb, whereas the measured fiducial cross section is 6.28 +/- 0.81(stat) +/- 0.69(syst) +/- 0.37(model) fb. The observed significance of the signal is 6.2 standard deviations above the background-only hypothesis.